IBM DS8000 Copy Services : updated for IBM DS8000 Release 9.1 - Dufrasne, Bertrand; Frankenberg, Michael (IT specialist); Eriksson, Tony (Storage specialist); Martinez, Lisa (Storage specialist); Fida, Suellen Ricardo (IT specialist); Riggins, Connie (Copy services specialist); Wells, Mark (IT specialist) (IBM redbooks., 2021)
This IBM® Redbooks® publication helps you plan, install, configure, and manage Copy Services on the IBM DS8000® operating in an IBM Z® or Open Systems environment. This book helps you design and implement a new Copy Services installation or migrate from an existing installation. It includes hints and tips to maximize the effectiveness of your installation, and information about tools and products to automate Copy Services functions. It is intended for anyone who needs a detailed and practical understanding of the DS8000 Copy Services. This edition is an update for the DS8900 Release 9.1. Note that the Safeguarded Copy feature is covered in IBM DS8000 Safeguarded Copy, REDP-5506.